Lite mer än bara könsorgan - Simon Ceder; Stina Westerlund (Utbildning & Demokrati)
”Somewhat more than mere genitalia” – Teaching at the crossroads of craft education and the knowledge area of sexuality, consent and relationships. This article explores teaching at the intersection of the knowledge area of sexuality, consent, and relationships, and the subject of crafts in lower secondary school. More specifically, it develops an understanding of subject-integrated teaching through embodied, material, and aesthetic processes in a cross-curricular context. The study is based on a craft teacher’s experiences from a teaching sequence in grade 9, where students designed and carved symbols related to sexuality, consent, and relationships in wood. The results highlight the impact of subject-integrated teaching and underscore student participation as pivotal, both in sexuality education and crafts. Another insight was the teacher’s ease in integrating the topic into craft education, where the craft’s focus on the process was contributory. The theme opened up the crafts classroom for existential exploration, fostered discussions, and created a more nurturing classroom environment.